A mixed-methods analysis of risk-reduction strategies adopted by syringe services program participants and non-syringe services program participants in New York City - Nisha Beharie; Adelya Urmanche; Alex Harocopos (BMC, 2023)
Abstract Background Since the emergence of fentanyl in the drug market, syringe services programs (SSPs) have been at the forefront of providing life-saving tools such as naloxone and fentanyl test strips to people who use drugs (PWUD). It is still unclear, however, how the adoption of risk-reduction practices has differed among PWUD in the context of increasing presence of non-pharmaceutical fentanyl in the drug supply. This study aims to assess the adoption of risk-reduction tools (e.g., naloxone) among those engaged with SSP services and those not engaged with SSP services. Methods We conducted a mixed-methods study following a convergent parallel design integrating both quantitative and qualitative data. Interviews were conducted with 80 people who used street opioids (i.e., heroin or opioid pills not prescribed), 32 of whom were not engaged in SSP services. Quantitative differences between those engaged and those not engaged in SSPs were assessed using independent samples t tests and Fisher's exact tests. A thematic analytic approach was employed to compare qualitative responses between the two groups. Results Three main themes emerged in our analysis: (1) Both groups expressed an interest in fentanyl test strips (FTS), but those engaged in SSP services found them to be more accessible; (2) there was greater adoption of and enthusiasm for naloxone among SSP participants; and (3) SSP participants were more likely to have or be interested in having someone check in on them when using alone, but stigma and perceived personal risk of overdose prevented widespread adoption of this practice among all participants. Conclusion SSPs provide a vital function by facilitating naloxone and FTS distribution to participants who often have little control over their exposure to fentanyl. However, stigma and misconceptions regarding drug use are barriers to people adopting risk-reduction practices, particularly among those not engaged with SSPs.